2012
DOI: 10.1007/s00894-012-1419-y
|View full text |Cite
|
Sign up to set email alerts
|

In silico and in vivo studies of an Arabidopsis thaliana gene, ACR2, putatively involved in arsenic accumulation in plants

Abstract: Previously, our in silico analyses identified four candidate genes that might be involved in uptake and/or accumulation of arsenics in plants: arsenate reductase 2 (ACR2), phytochelatin synthase 1 (PCS1) and two multi-drug resistant proteins (MRP1 and MRP2) [Lund et al. (2010) J Biol Syst 18:223-224]. We also postulated that one of these four genes, ACR2, seems to play a central role in this process. To investigate further, we have constructed a 3D structure of the Arabidopsis thaliana ACR2 protein using the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…Because AtACR2 and AtHAC1 share sequence identity within the region used by Dhankher et al (2006) to knock down expression of AtACR2 by RNA interference, this sequence may also have suppressed AtHAC1 expression in their RNAi lines, thus resulting in decreased As(V) tolerance and As hyperaccumulation in the shoots (Chao et al, 2014). Nahar et al (2012) reported increased As(V) sensitivity and As accumulation in the shoots of a single T-DNA line (SALK_005882C) with a T-DNA insertion to the neighboring gene (At5g03452) of AtACR2 (At5g03455), which appeared to knockdown the expression of AtACR2.…”
Section: Discussionmentioning
confidence: 99%
“…Because AtACR2 and AtHAC1 share sequence identity within the region used by Dhankher et al (2006) to knock down expression of AtACR2 by RNA interference, this sequence may also have suppressed AtHAC1 expression in their RNAi lines, thus resulting in decreased As(V) tolerance and As hyperaccumulation in the shoots (Chao et al, 2014). Nahar et al (2012) reported increased As(V) sensitivity and As accumulation in the shoots of a single T-DNA line (SALK_005882C) with a T-DNA insertion to the neighboring gene (At5g03452) of AtACR2 (At5g03455), which appeared to knockdown the expression of AtACR2.…”
Section: Discussionmentioning
confidence: 99%
“…), which has important implications for how As is redistributed within the plants (Zhao et al 2009). Previously, by employing the in silico and in vivo studies on A. thaliana, we have postulated that the AtACR2 gene is involved in reduction of arsenate (AsV) to arsenite (AsIII) in the plant cells (Nahar et al 2012). One advantage of this explanation is that arsenite (but not arsenate) can be sequestered in the vacuoles of the plant cells although it is more toxic than AsV (Cobbett 2000;Mukhopadhyay et al 2000;Dhankher et al 2006;Blum et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…PCR tubes containing the reaction mixture were then placed in the thermocycler (Flexcycler, model: Block assembly 96G). The RT-PCR cycle setups for the first strand cDNA synthesis and the second strand DNA synthesis were carried out as described by Nahar at al. (2012).…”
Section: Analysis Of Gene Expression By Rt-pcrmentioning
confidence: 99%
See 2 more Smart Citations